Acetic acid fermentation of soybean molasses and characterisation of the produced vinegar - Miranda, Lucas Caldeirão Rodrigues (Array, 2020)
Soybean molasses is a by-product from the production of protein concentrate from soybean meal that predominantly contains sugars, with sucrose as the major component. In Brazil, soybean molasses is used for animal feed or it is discarded, although some industries use it to produce ethanol. This study aims to evaluate the parameters required for the acetic acid fermentation of soybean molasses, and characterise the resultant vinegar. To study the most suitable parameters for the acetic acid fermentation, vinegar was produced from the alcoholic fermentation of soybean molasses through eight fermentation cycles: five for adaptation and three for production. The average acidity of the acetic acid fermentation product was 50.60 g/L, with an acetic acid fermentation yield, total yield of acetic acid in broth and productivity 65.01 %, 92.76 % and 0.033 g/(L·h), respectively. The vinegar produced from soybean molasses had an acidity of 5.07 % (m/V), residual ethanol content 0.17 % (m/V), sugars 7.86 % (m/V), dry extract 14.67 % (m/V), ash 2.27 % (m/V) and a density of 1.023 g/cm3. The contents of total phenolics and isoflavone decreased after the alcohol and acetic acid fermentations. Moreover, the isoflavone profile of the fermented product comprised only three forms: daidzein, glycitin and genistin. According to our results, 3460 L of vinegar can be produced for every tonne of soy molasses, with an acetic acid concentration of 40 g/L, the minimum required by the legislation on vinegar production. Thus, these findings demonstrate that soy molasses represents a useful raw material for the production of vinegar.